Targeting Dendritic Cell Function during Systemic Autoimmunity to Restore Tolerance - Mackern-Oberti, Juan P. (MDPI, 2014)
Systemic autoimmune diseases can damage nearly every tissue or cell type of the body. Although a great deal of progress has been made in understanding the pathogenesis of autoimmune diseases, current therapies have not been improved, remain unspecific and are associated with significant side effects. Because dendritic cells (DCs) play a major role in promoting immune tolerance against self-antigens (self-Ags), current efforts are focusing at generating new therapies based on the transfer of tolerogenic DCs (tolDCs) during autoimmunity. However, the feasibility of this approach during systemic autoimmunity has yet to be evaluated. TolDCs may ameliorate autoimmunity mainly by restoring T cell tolerance and, thus, indirectly modulating autoantibody development. In vitro induction of tolDCs loaded with immunodominant self-Ags and subsequent cell transfer to patients would be a specific new therapy that will avoid systemic immunosuppression. Herein, we review recent approaches evaluating the potential of tolDCs for the treatment of systemic autoimmune disorders.